Large-cell neuroendocrine carcinoma of the gynecologic tract: Prevalence, survival outcomes, and associated factors - Pang, Li; Chen, Jie; Chang, Xiaohan (Frontiers in Oncology, 2022)
Background: We aimed to assess the clinical behavior of gynecologic large-cell neuroendocrine carcinoma (LCNEC) via a retrospective analysis of data from 469 patients. Methods: Patients diagnosed with gynecologic LCNEC from 1988 to 2015 were identified using the Surveillance, Epidemiology, and End Results database. Univariate and multivariate Cox hazard regression analyses were performed to assess independent predictors of overall survival (OS) and cancer-specific survival (CSS). OS and CSS were also evaluated using the Kaplan–Meier method, and the effects of different treatment regimens on prognosis were compared according to disease stage. Results: Cervical, ovarian, and endometrial LCNEC were observed in 169, 219, and 79 patients, respectively. The five-year OS rates for patients with cervical, ovarian, and endometrial LCNEC were 35.98%, 17.84%, and 23.21%, respectively, and the median duration of overall survival was 26, 11, and 11 months in each group. The five-year CSS rates for the three groups were 45.23%, 19.23%, and 31.39%, respectively, and the median duration of CSS was 41, 12, and 11 months in each group. Multivariate analysis revealed that American Joint Committee on Cancer stage, lymph node metastasis, and chemotherapy were independent prognostic factors for overall survival and CSS in patients with cervical LCNEC. Lymph node metastasis, surgery, and chemotherapy were independent prognostic factors for overall survival and CSS in the ovarian group and for overall survival in the endometrial group. Lymph node metastasis and surgery were also independent prognostic factors for CSS in the endometrial group. Conclusion: Surgery alone may help to improve overall survival and CSS in patients with early-stage cervical LCNEC. In contrast, surgery+chemotherapy and surgery+radiotherapy may help to improve survival for early-stage ovarian and endometrial LCNEC, respectively. Regardless of subtype, comprehensive treatment with surgery, CTX, and RT should be considered to improve prognosis in patients with advanced-stage gynecologic LCNEC.